Integrated marketing communication: an insight into its evolution - Mokhtar, Aida (2018)
Integrated marketing communication (IMC) relates to the promotional component of the marketing mix comprising product, price, place and promotion. The ability of IMC in affecting the sales of products underscores its important role in bringing together marketers and buyers at the marketplace. Its elusiveness is ostensible yet intriguing as the literature reveals that IMC is relatively a new area of study, there is no agreement on what it is and what benefits it offers, there is the lack of clarity in its definition, limitations in its application, and the apparent dearth of a theoretical foundation. Nevertheless, IMC could be effective with the right amalgamation of marketing communication tools that embraces the strengths of advertising, public relations, direct marketing and promotions and other tools in a complementary manner to achieve goals that could include purchase. There is also the perceptible common thread of integration that runs through the various semantics of IMC found in the literature. The study used a meta-ethnographic synthesis approach in its qualitative research design when reviewing previous literature on IMC. The paper would be of profound interest to academicians and practitioners who yearn for an examination on IMC definitions and theories.